Redefining Pre-Indo-European Language Families of Bronze Age Western Europe: A Study Based on the Synthesis of Scientific Evidence From Archaeology, Historical Linguistics and Genetics - Horvath, Csaba Barnabas (European Scientific Journal, ESJ, 2019)
When and how did the Indo-European language family expand into western Europe? What language families were present there before, and where did they come from? Where does Basque and Etruscan come from? These are questions and puzzles that have been in the focus of the archaeological community since long ago. The present paper offers a coherent hypothesis mapping the expansion of language families in the western half of Europe from the Copper Age till the Roman conquest, based on matchings identifies between the newest genetic evidence, and earlier results of archaeology and historical linguistics. The approach focuses on matching phylogenetic and geographical distribution patterns of Y-DNA lineages with archaeological cultures, and the phylogenetics of language families in order to identify migrations and language families in Western Europe in the 3 rd -1 st millennia BCE.